2008
DOI: 10.1161/strokeaha.107.499483
|View full text |Cite
|
Sign up to set email alerts
|

Mild Induced Hypertension Improves Blood Flow and Oxygen Metabolism in Transient Focal Cerebral Ischemia

Abstract: Background and Purpose-In focal ischemic cortex, cerebral blood flow autoregulation is impaired, and perfusion passively follows blood pressure variations. Although it is generally agreed that profound hypotension is harmful in acute stroke, the hemodynamic and metabolic impact of increased blood pressure on the ischemic core and penumbra are less well understood. We, therefore, tested whether pharmacologically induced hypertension improves cerebral blood flow and metabolism and tissue outcome in acute stroke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
95
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(100 citation statements)
references
References 57 publications
5
95
0
Order By: Relevance
“…They stated that the reason for cerebral oxygen saturation being higher in patients undergoing general anesthesia than those undergoing spinal anesthesia was the suppression of cerebral metabolism by the general anesthesia. In a study, in focal cerebral ischemia produced by distal middle cerebral artery occlusion in mice, it was shown that mild induced hypertension produced by phenylephrine rapidly increased cerebral blood flow and cerebral oxygen saturation and it was also shown that hypotension had a negative effect on the cerebral oxygen saturation (22). In our study, blood pressures in the two groups were normal.…”
Section: Discussionsupporting
confidence: 53%
“…They stated that the reason for cerebral oxygen saturation being higher in patients undergoing general anesthesia than those undergoing spinal anesthesia was the suppression of cerebral metabolism by the general anesthesia. In a study, in focal cerebral ischemia produced by distal middle cerebral artery occlusion in mice, it was shown that mild induced hypertension produced by phenylephrine rapidly increased cerebral blood flow and cerebral oxygen saturation and it was also shown that hypotension had a negative effect on the cerebral oxygen saturation (22). In our study, blood pressures in the two groups were normal.…”
Section: Discussionsupporting
confidence: 53%
“…Blood flow to the ischemic penumbra is known to be CPP dependent as normal cerebral blood flow autoregulation is lost in the ischemic penumbra, 24 so ICP elevation would be predicted to reduce penumbral perfusion. The principle of increasing CPP to enhance collateral flow and penumbral perfusion has been exploited in several clinical trials; [25][26][27][28][29][30][31] however, to date, these have all focused on mean arterial pressure (MAP) rather than intracranial pressure (CPP = MAP − ICP).…”
Section: Discussionmentioning
confidence: 99%
“…29 In addition, blood pressure and blood gases are important confounders of outcome and need to be monitored. 30,31 The use of quick and minimal invasive methods (non-invasive blood pressure measurement, suitable and easy accessible blood collection sites) is recommended. The choice of the anaesthetic is also highly important, as some may have neuroprotective effects, and/or be vasodilators, as for example Isoflurane.…”
Section: Discussionmentioning
confidence: 99%